1995
DOI: 10.1002/cne.903600406
|View full text |Cite
|
Sign up to set email alerts
|

Development of parvalbumin immunoreactivity in the chick Edinger Westphal nucleus

Abstract: To determine when the calcium-binding protein parvalbumin appears during development, neurons in the chick Edinger Westphal nucleus were examined for parvalbumin immunoreactivity at a variety of embryonic stages. Parvalbumin immunoreactivity appeared on embryonic day 14 (E14, Hamburger and Hamilton stage 40) in predominantly lateral Edinger Westphal neurons.Cytochrome oxidase activity within the nucleus was examined throughout development, as an indicator of physiological activity, and expression of cytochrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Developmental studies in embryonic chickens have shown that EW neurons are electrophysiologically active at E12, as revealed by cytochrome oxidase activity, and also at that age develop voltage-activated calcium currents [10]. At E14, an increase in parvalbumin occurs in EW neurons, without any further change in voltage-activated calcium currents [8,9,10].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Developmental studies in embryonic chickens have shown that EW neurons are electrophysiologically active at E12, as revealed by cytochrome oxidase activity, and also at that age develop voltage-activated calcium currents [10]. At E14, an increase in parvalbumin occurs in EW neurons, without any further change in voltage-activated calcium currents [8,9,10].…”
mentioning
confidence: 99%
“…At E14, an increase in parvalbumin occurs in EW neurons, without any further change in voltage-activated calcium currents [8,9,10]. These investigators suggested that the expression of parvalbumin at E14 might occur due to, or in association with, the addition of a calcium conducting channel at E14 [10].…”
mentioning
confidence: 99%
See 3 more Smart Citations